PELATIHAN STRATEGI DIGITAL MARKETING BAGI USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KECAMATAN SARJO (MEMBENTUK DAN MENDUKUNG PENGEMBANGAN WIRAUSAHAWAN MUDA DAN PEMULA) - Nuraisyah, Nuraisyah; Haryono, Dandan; Lutfiani, Lutfiani (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2023)
Small businesses have an important and significant role in the economy of Sarjo District, as well as a provider of employment. Although they do not face capital problems, small companies face challenges in marketing, workforce, technology, people skills, and networks. This study aims to describe and analyze small businesses in Sarjo District by using a qualitative approach and inductive method, as well as case study and outreach strategies. The focus of this research is aimed at small businesses in Sarjo District and related parties as targets. Data was collected through observation, interviews, document collection, and outreach. Data analysis techniques include data collection, data condensation, and drawing conclusions. The results of the study show that digital marketing strategies for small businesses are not optimal due to limited resource capacity. This is caused by the orientation of business owners who are more focused on production without regard to market opportunities and lack of knowledge in running a business. The lack of follow-up stages such as technical guidance and business assistance in Sarjo District is also an obstacle, especially in personal development through an understanding of digital marketing. Based on the results of field research on small businesses in Sarjo District, it appears that entrepreneurial abilities such as enthusiasm, attitudes, actions, and knowledge in running a business are still weak. Networking is also identified as an important aspect for the survival and resilience of small businesses in the region. Thus, this service aims to provide solutions and education through comprehensive digital marketing training for small and medium business actors and prospective novice entrepreneurs.